Tobacco Smoke Pollution in Hospitality Venues Before and After Passage of Statewide Smoke‐Free Legislation. Issue 2 (10th October 2016) - Buettner‐Schmidt, Kelly; Boursaw, Blake; Lobo, Marie L.; Travers, Mark J.
Abstract: Objective: In 2012, North Dakota enacted a comprehensive statewide law prohibiting smoking in enclosed public places. Disparities in tobacco control exist in rural areas. This study's objective was to determine the extent to which the passage of a comprehensive, statewide, smoke‐free law in a predominantly rural state influenced tobacco smoke pollution in rural and nonrural venues. Design and Sample: A longitudinal cohort design study comparing the levels of tobacco smoke pollution before and after passage of the statewide smoke‐free law was conducted in 64 restaurants and bars statewide in North Dakota. Measures: Particulate matter with a median aerodynamic diameter of <2.5 μm (a valid atmospheric marker of tobacco smoke pollution) was assessed. Results: A significant 83% reduction in tobacco smoke pollution levels occurred after passage of the law. Significant reductions in tobacco smoke pollution levels occurred in each of the rural categories; however, no difference by rurality was noted in the analysis after passage of the law, in contrast to the study before passage. Conclusions: To our knowledge, this was the largest, single, rural postlaw study globally. A comprehensive statewide smoke‐free law implemented in North Dakota dramatically decreased the level of tobacco smoke pollution in bars and restaurants.